RESHAPES: Increasing AAST EGS grade is associated with anastomosis type. Issue 6 (June 2018) - Hernandez, Matthew C.; Bruns, Brandon R.; Haddad, Nadeem N.; Lauerman, Margaret; Morris, David S.; Arnold, Kristen; Phelan, Herb A.; Turay, David; Murry, Jason; Oh, John S.; Enniss, Toby; Carrick, Matthew M.; et al.
Abstract : INTRODUCTION: Threatened, perforated, and infarcted bowel is managed with conventional resection and anastomosis (hand sewn [HS] or stapled [ST]). The SHAPES analysis demonstrated equivalence between HS and ST techniques, yet surgeons appeared to prefer HS for the critically ill. We hypothesized that HS is more frequent in patients with higher disease severity as measured by the American Association for the Surgery of Trauma Emergency General Surgery (AAST EGS) grading system. METHODS: We performed a post hoc analysis of the SHAPES database. Operative reports were submitted by volunteering SHAPES centers. Final AAST grade was compared with various outcomes including duration of stay, physiologic/laboratory data, anastomosis type, anastomosis failure (dehiscence, abscess, or fistula), and mortality. RESULTS: A total of 391 patients were reviewed, with a mean age (±SD) of 61.2 ± 16.8 years, 47% women. Disease severity distribution was as follows: grade I (n = 0, 0%), grade II (n = 106, 27%), grade III (n = 113, 29%), grade IV (n = 123, 31%), and grade V (n = 49, 13%). Increasing AAST grade was associated with acidosis and hypothermia. There was an association between higher AAST grade and likelihood of HS anastomosis. On regression, factors associated with mortality included development of anastomosis complication and vasopressor use but not increasing AAST EGS grade or anastomotic technique. CONCLUSION: This is the first study to use standardized anatomic injury grades for patients undergoing urgent/emergent bowel resection in EGS. Higher AAST severity scores are associated with key clinical outcomes in EGS diseases requiring bowel resection and anastomosis. Anastomotic-specific complications were not associated with higher AAST grade; however, mortality was influenced by anastomosis complication and vasopressor use. Future EGS studies should routinely include AAST grading as a method for reliable comparison of injury between groups. LEVEL OF EVIDENCE: Prognostic, level III. Abstract : Supplemental digital content is available in the text.